2004
DOI: 10.1097/01.mrr.0000127639.47494.e3
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving problems and feelings experienced by family caregivers of stroke survivors the first month after discharge

Abstract: The purpose of this study was to identify the major problems and associated feelings experienced by family caregivers of stroke survivors during the first month after returning home. Safety, difficulty in managing activities of daily living, and cognitive, behavioral and emotional changes of stroke survivors (for example, mood swings, lack of motivation, forgetfulness and memory loss, depression and calling the caregiver often) were the three most common problems experienced by caregivers during the first mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 24 publications
4
116
1
3
Order By: Relevance
“…A longitudinal study would permit a much stronger assessment of the intervention. Research has suggested that the first month postdischarge is one of the most stressful periods for stroke caregivers because that is when the limitations of the individual with stroke become salient [10]. As a result of this process, major changes in caregiver mental health in our study were likely occurring during the 3-month follow-up interval.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A longitudinal study would permit a much stronger assessment of the intervention. Research has suggested that the first month postdischarge is one of the most stressful periods for stroke caregivers because that is when the limitations of the individual with stroke become salient [10]. As a result of this process, major changes in caregiver mental health in our study were likely occurring during the 3-month follow-up interval.…”
Section: Discussionmentioning
confidence: 88%
“…Managing multiple psychosocial changes in the first month postdischarge is often very difficult [10], and research supports the need for interventions during the immediate postdischarge period [11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies show caregivers sustain negative psychological effects during the first year after a stroke survivor is discharged home (Blake, Lincoln, & Clarke, 2003;Burton, 2000;Clark & Smith, 1998;Coombs, 2007;Grant et al, 2004;Ski & O'Connell, 2007). Recent research finds stroke survivors often do not reach their rehabilitation goals and lack of information is a major barrier to continued recovery (Jones, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Stroke survivors and their caregivers have difficulty obtaining information about their condition (Andersen et al, 2000), managing special cognitive and behavioral problems without assistance (Grant, Glandon, Elliott, Giger, & Weaver, 2004), and obtaining access to community and rehabilitation services (Ski & O'Connell, 2007). In a National Stroke Association survey, 38% of long-term stroke survivors reported a lack of information about community and rehabilitation resources (Jones, 2006).…”
Section: Literaturementioning
confidence: 99%
“…However, being part of the immediate environment of the individual with stroke, spouses are at risk of disrupting their own participation level. There is clear evidence of an increased prevalence of burden [4,5,6,7,8,9,10,11] and depression [12,13,14,15] among caregivers of stroke survivors but no data are available on changes in their participation level. A clearer understanding of which participation domains are most affected after a spouse’s stroke is essential to developing strategic interventions to support these spouses in the accomplishment of meaningful activities and roles where they need it most.…”
Section: Introductionmentioning
confidence: 99%